Seasonal structure of water stages on lakes in Northern Poland - Plewa, Katarzyna; Wrzesiński, Dariusz; Ptak, Mariusz (Bulletin of Geography. Physical Geography Series, 2018)
The paper presents the characteristics of hydrological periods in an average annual cycle in Polish lakes. The type of periods and their sequence determine the regime of water stages in lakes. The article applies the unsupervised approach of analysis of the pattern of water level fluctuations, where the identification of the regime is performed through grouping analytical parameters. Hydrological periods were designated by means of grouping elementary time units of the hydrological year (pentads) based on the similarity of their parameters, namely the distributions of water level frequencies. The analysis covered daily water stages in 33 lakes in Poland from the period from 1984 to 2013. Five types of hydrological periods were designated. The studied lakes differ in the number, type, and sequence of hydrological periods in an average annual cycle. The most abundant group of 19 lakes includes lakes with a 4-period temporal structure of water stages with the course of water stages in a year characteristic of this geographical zone. No spatial patterns occurred in terms of location of lakes from particular groups. This suggests the dominant role of local factors determining the seasonality of water stages.